Pandangan Islam Terhadap Pengembangan Dan Pemanfaatan Sains Dan Teknologi - Anas Suprapto; Yulianto Yulianto (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2023)
The development and use of technology as a human activity in the perspective of Islamic jurisprudence is included in the category of something that is subject to law. So this activity must also be closely related to Islamic law itself, starting from taklifi law to wadl'i law. This research is a literature study. In data collection techniques, the authors explore scientific papers as well as several credible sites that discuss topics regarding Islam and technology, such as credible news sites, scientific papers obtained from several journals, both from Islamic journals. as well as universal journals such as the Technology Journal. The results of this discussion show that, 1. Islamic Views in the Development and Utilization of Science and Technology, including: a) Islamic views in the Development and Utilization of Science and Technology, studying and developing a technology as a tool for the benefit of human life has several advantages starting from fiqh law , moral values, to evidence of servitude to Allah SWT. b) Shari'a Goals in the Development and Utilization of Technology. In summary, if a technology has become a medium/tool in realizing the needs of human life: primary, secondary, and tertiary needs, then the law of technological development which was originally fardu kifayah can turn into fardu ain, sunah, and as a priority. c) The Islamic view on the use or use of technology, the use or use of technology is very close to the purpose of using the technology itself. d) The Polemic on the Use of Loudspeaker Technology (Toa), the use of loudspeakers in the range of 100 db as stated by the Minister of Religion in his circular letter is makruh, it can even be illegal. 2. Development and utilization of science and technology in terms of benefit and resistance to damage in Islam, including: a) Maslahat and Mafsadat levels, religious orders to create benefit are orders to realize various good deeds (al-ihsānu). While the essence of good deeds is the activity of realizing benefit and resisting damage. b) How to determine Benefit and Harm, Ukhrowi, Shari'a (an-Naqlu wa asSyar`i) and Worldly, Intellect, experimentation, and customs (al-`aqlu wa at- Tajarrubu Wa al-Ādatu) c) Charities Human Actions in the Perspective of Generating Benefit and Rejecting Damage, Benefit (al-maṣlahatu), Cause of worldly benefit, Cause of ukhrowi benefit and Cause of worldly and ukhrowi benefit ) Science and Technology as Tools and Media to Realize Benefit and Refuse Damage, media law is in harmony with the law of the purpose of using the media itself. If the goal is unlawful, makruh, obligatory mubah, or sunna, then media law and the cause is also unlawful, makruh, mubah, obligatory, or sunnah